Comptence-based assessment as inputs into food service curriculum development - Dones, Mary Jane M.
This descriptive research case study aimed to provide empirical competence-based assessment data on managers in selected fastfood operations, which will provide valuable inputs for foodservice curriculum development. The study also attempted to determine the managerial tasks performed by fastfood managers in doing their jobs and the foodservice competencies associated with the managerial tasks. Three fastfood establishments were selected based mainly on their classification in terms of number of stores operating nationwide and their willingness to participate in the study. Survey-interview, on-site observation and focus group discussion were the methodologies used to gather information about the foodservice establishments. Results of the study revealed that managerial tasks performed by fastfood managers were classified mainly into: Managing the shift, Administrative duties and Other Managerial Tasks. The study identified 14 specific foodservice competencies classified into Human, Technical Management and Conceptual Skills which can be used as inputs into foodservice curriculum development. Human Skills include Customer Relations, Employee Relations, Leadership Skills, Building Teamwork, Communication Skills and Motivating Others. The Technical Management Skills are Result Orientation, Managing Performance, Production Efficiency, Flexibility and Decisiveness, Concern for Quality and Technical Expertise. Conceptual Skills include two value skills: Dedication and Commitment, and Sense of Ownership. The study recommends that educational institutions offering foodservice management should incorporate Human and Technical Management Skills and the values of dedication and commitment and sense of ownership in the development of foodservice curriculum. Faculty members should have actual exposure on foodservice operation to impart lessons more effectively. Educators must initiate ways to strengthen relationships between the academe and the industry to lessen the gap between graduates of foodservice management programs and manpower requirements of the industry. Further research on competencies in other foodservice segments is also recommended.